Use of linear measurements in a regression equation to predict ribeye area - Waylan, A.T.; Campbell, R.E.; Unruh, John A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Thirty beef carcasses were used to test the accuracy of three regression equations to predict ribeye area (REA) and to compare several strategies to rapidly estimate REAs. Linear measurements, USDA grids, and Video Image Analysis (VIA) were used to determine REA from both right and left carcass sides. Ribeye areas measured by USDA grids and estimated by regression equations were highly correlated (r>.94) with REA measured by VIA. Regression equations using linear measurements and USDA grids were equally (P=.73) accurate in predicting VIA REA. Furthermore, REA from either the left or the larger (right or left) carcass sides accurately predicted the VIA REA from the larger carcass side. Therefore, in commercial packing facilities where chain speed may limit the opportunity to accurately grid or measure ribeyes, the linear measurements of left side ribeye length and widest-width can be collected and used in a regression equation to accurately predict the larger REA to be used in calculating yield grade.
Keywords: Beef; Ribeye area; USDA ribeye grids; Linear measurements